Formation of porous SnS nanoplate networks from solution and their application in hybrid solar cells - Rath,T; Gury,L; Sanchez-Molina,I; Martinez,L; Haque,SA (Chemical Communications, 2015)
Herein, we present a facile solution-based route towards nanostructured, hybrid absorber layers based on tin mono-sulfide (SnS), an emerging, non-toxic absorber material for low-cost and large-scale PV applications. Charge photogeneration properties in the hybrid system are studied using transient absorption spectroscopy and fabricated solar cells show efficient photocurrent generation over a broad spectral range.